Rencana Pembelajaran Semester sebagai Pemandu dan Belenggu Proses Pembelajaran - Nugraha Pranadita; Syamsu Yusuf (Jurnal Pendidikan Edutama, 2022)
Abstract: Lecturers have the obligation to determine and develop the RPS (Semester Learning Plan) for each subject they are taught. RPS is a guide for the learning process as well as a shackle for the learning process because of its various limitation or limitations. The success of the RPS is determined by the achievement of its CPL (Graduate Learning Outcomes) which is in accordance with the KKNI (Indonesian National Qualification Framework) that has been determined. The purpose of this research was to prove that the RPS apart from being a guide for the learning process as well as a shackle for the learning process itself for various reasons, so that the CPL  may not be achieved. This research is a qualitative descriptive research. Descriptive research is non-experimental, the aim is to obtain detailed information about the problem being researched. The data collection technique in qualitative descriptive research was carried out by means of triangulation (a combination of several data collection techniques), while data analysis was carried out deductively. The results of this research are that there are three things that can be the shackles of the learning process so that CPL may not be achieved, namely; (1) the characteristics of the learning process are rigid, (2) the time for reviewing and adjusting the RPS is not determined, and (3) the substance of the subject matter is static.Keyword: RPS, learning, CPL, and KKNI. Abstrak: Dosen mempunyai kewajiban untuk menetapkan dan mengembangkan RPS (Rencana Pembelajaran Semester) untuk setiap mata kuliah yang diampunya. RPS merupakan pemandu proses pembelajaran sekaligus sebagai belenggu proses pembelajaran karena berbagai batasan atau keterbatasan yang dimilikinya. Keberhasilan RPS ditentukan dengan pencapaian CPL (Capaian Pembelajaran Lulusan)-nya yang bersesuaian dengan KKNI (Kerangka Kualifikasi Nasional Indonesia) yang telah ditetapkan. Tujuan dari penelitian ini adalah untuk membuktikan bahwa RPS selain sebagai pemandu proses pembelajaran sekaligus sebagai belenggu bagi proses pembelajaran itu sendiri karena berbagai hal, sehingga CPL dimungkinkan tidak tercapai. Penelitian ini merupakan penelitian deskriptif kualitatif. Penelitian deskriptif bersifat non-eksperimen, tujuannya untuk mendapatkan informasi yang detail tentang permasalahan yang diteliti. Teknik pengumpulan data pada penelitian deskriptif kualitatif dilakukan dengan cara triangulasi (gabungan beberapa teknik pengumpulan data), sementara itu analisis data dilakukan secara deduktif. Hasil penelitian ini adalah terdapat tiga hal yang dapat menjadi belenggu proses pembelajaran sehingga CPL dimungkinkan tidak tercapai, yaitu; (1) karakteristik proses pembelajaran yang bersifat rigid, (2) tidak ditentukannya waktu peninjauan dan penyesuaian RPS, dan (3) adanya substansi materi mata kuliah yang bersifat statis.Kata kunci: RPS, pembelajaran, CPL, dan KKNI.